Efficacy of single dose of 800μg of misoprostol in first trimester abortion - Subedi, Shanti (Journal of Nobel Medical College, 2012)
Objective: To assess the efficacy, safety and cost effectiveness of Misoprostol (Prostaglandin E1 analogue) as a single dose of 800?g in first trimester abortion Methods: A descriptive study was conducted in Nobel Medical College and Teaching Hospital from June 2010-June 2011 where 110 patients were enrolled for first trimester abortions including incomplete, missed, blighted ovum. Each woman received a single dose of 800?g of Misoprostol intravaginally and the the process of abortion was monitored to assess the outcome measures. Results: Successful abortion was seen in 102 patients (92.7%) with induction to delivery interval of < 24 hours and the remaining 8 (7.2%) of them had to undergo surgical evacuation. Side effects noted were lower abdominal pain, fever, nausea, vomiting, and diarrhoea. Mean hospital stay of the patients was 48 hours. Conclusion: Misoprostol is a safe, cost effective and efficacious drug for first trimester abortion even as a single dosage. DOI: http://dx.doi.org/10.3126/jonmc.v1i2.7293 Journal of Nobel Medical College (2012), Vol.1 No.2 p.11-13